Motives for choice of work in healthcare and individual performance of medical doctors working in public multispecialty hospitals in Warsaw - Malgorzata Chmielewska; Jakub Stokwiszewski; Justyna Markowska; Tomasz Hermanowski (Frontiers in Medicine)
ObjectiveThis study explores the relationship between the motives driving people to work in healthcare and the individual work performance of public hospital doctors. The results are analyzed in terms of changes necessary to improve work performance among medical practitioners.MethodsA cross-sectional study was conducted among 249 medical doctors from 22 randomly selected inpatient departments of multidisciplinary public hospitals in Warsaw. Data were collected using self-administered structured questionnaires developed by WHO. Herzberg model as modified by the authors was used to identify key motives for choosing a job in healthcare. A chi-square test was used to analyze the correlations between the reasons for choosing to work as a medical practitioner and socio-demographic variables. The interdependence between individual performance and the main reason for choosing a career in healthcare was examined with a Kruskal-Wallis test.ResultsThe research results indicate a statistically significant relationship between the main motive for choosing a career in healthcare—namely, the individual motivation of hospital doctors, and individual work performance as measured by “notion that my work is valuable in itself” (p = 0.003) and “responsibility for outcomes” (p = 0.024) response categories. Doctors whose main motive for choosing the profession was to help patients are more likely to feel high satisfaction with “The notion that my work is valuable in itself” than others (42.5% vs. 27.0% for “other” and 28.3% for “Nature of the work itself”) and with “The sense of responsibility for the outcomes” (50.0% vs. 35.1% for “other” and 36.3% for “Nature of the work itself”).ConclusionsWhen examining factors affecting the professional performance of medical doctors, aspects related to the original main motive for choosing this profession and for working in the healthcare must not be disregarded. The distinctive features of this profession, including personal qualities, should perhaps be considered in the admission criteria for medical studies.